A Movie Recommender System: BIG SCREEN - Gupta, Akash (Journal of Advanced Research in Information Technology, Systems and Management; Vol 4 No 1 (2020): Journal of Advanced Research in Information Technology, Systems & Management, 2021)
- Presently a day's suggestion framework has changed the style of looking through the things of our advantage. This is data sifting approach that is utilized to anticipate the inclination of that user. The most well-known zones where recommender framework is applied are books, news, articles, music, recordings, motion pictures and so on. In this paper we have proposed a film suggestion framework named BIG SCREEN. It depends on community oriented sifting approach that utilizes the data gave by clients, breaks down them and afterward suggests the films that is most appropriate to the client around then. The prescribed film list is arranged by the appraisals given to these motion pictures by past clients and it utilizes K-implies calculation for this reason. BIG SCREEN likewise help clients to discover the films of their decisions dependent on the film understanding of different clients in productive and powerful way without burning through much time in pointless perusing. This framework has been created in PHP utilizing Dreamweaver 6.0 and Apache Server 2.0. The introduced recommender framework produces proposals utilizing different sorts of information and information about clients, the accessible things, and past exchanges put away in modified databases. The client would then be able to peruse the proposals effectively and discover a film of their decision. How to cite this article: Gupta A, Gupta A. A Movie Recommender System: BIG SCREEN. J Adv Res Info Tech Sys Mgmt 2020; 4(1): 9-13